Generations and Protest in Eastern Germany: Between Revolution and Apathy - Philippe Joly (Comparative Sociology, 2018)
How is the protest behavior of citizens in new democracies influenced by their experience of the past? Certain theories of political socialization hold that cohorts reaching political maturity under dictatorship are subject to apathy. Yet, it remains unclear whether mobilization during the transition can counterbalance this effect. This article examines the protest behavior of citizens socialized in Eastern Germany, a region marked by two legacies: a legacy of autocracy and, following the 1989-90 revolution, a legacy of transitional mobilization. Using age-period-cohort models with data from the European Social Survey, the analysis assesses the evolution of gaps in protest across generations and time between East and West Germans. The results demonstrate that participation in demonstrations, petitions, and boycotts is lower for East Germans socialized under communism in comparison with West Germans from the same cohorts. This participation deficit remains stable over time and even increases for certain protest activities.
Keywords: 330; political participation; protest; political socialization; democratization; Eastern Germany